Income Assistance (the ODSP) and Disabled Women in Ontario, Canada: Limited Program Information, Restrictive Incomes and the Impacts Upon Socio-Spatial Life - Crooks, Valorie A. (Disability Studies Quarterly, 2004)
Women who live with an illness or impairment are an extremely marginalized and impoverished group of citizens in the province of Ontario, Canada. All too often they lack the resources that would enable them to improve their everyday lives such as employment or simply higher amounts of income assistance. The purpose of this paper is to illustrate some of the complex ways in which one's status as both an income assistance recipient and as a woman living with an illness or impairment that results in disability impacts upon everyday life. In this paper I focus specifically on experiential evidence shared during in-depth interviews conducted with 10 women receiving Ontario Disability Support Program (ODSP) support residing throughout the province of Ontario, Canada. I show how both the restrictive amounts of monies afforded to recipients and the limited amounts of information shared with them about key ODSP aspects such as transportation reimbursements significantly impact upon the women's abilities to move around in everyday society and space, which in turn imposes limitations on both their social and spatial lives.